COMPARATIVE REVIEW OF THE CONJUNCTIONS IN THE TRANSLATIONS OF THE NEW TESTAMENT IN CONTEMPORARY MACEDONIAN LANGAUGE WRITTEN WITH GREEK ALPHABET (Philological Studies, 2019)
The subject of this paper are the first translations of the New Testament in Macedonian contemporary language from the 18th and the 19th centuries: The Konikovo Gospel, The Kulakia Gospel, The Boboščica Gospel and the Trlis Gospel. They are all written in Greek alphabet and each of them is related to a specific dialect of the South-Eastern group of Macedonian dialects. In the paper, we present the conjunctions found in the readings common for all of the four analyzed texts. Firstly, the conjunctions used in each of the texts are given in a table; afterwards, a comparative analysis is provided, focusing on whether the frequency and the usage of the conjunctions match the corresponding patterns in the different dialects to which they are related to or if they show certain differences and/or stylizations.
Keywords: conjunctions, comparison, New Testament, contemporary Macedonian language, Greek alphabet